PROTOTYPE PENGUKUR KELEMBABAN TANAH DAN INTENSITAS CAHAYA BERBASIS ARDUINO UNO - Dimas Panji Wira Hardi; Hamzah Afandi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Innovation is a goal that can play a critical role in the world of technological development, one of which is as a measuring tool for both technical and non- technical fields, among them is to measure moisture in the soil and the sunlight needed by plants in agriculture. This tool requires basic components in the form of Arduino Uno, copper plate, iron plate, non-inverting op-amp circuit, LDR, 16x2 LCD, and a 5V power source. Arduino Uno itself serves as the main control on the tool, LDR, copper plate and iron input block as a reader of moisture content in the soil and sunlight intensity, also 16x2 LCD as an output produ d then yed by . block to determine humidity and light intensity. The copper and iron plates will read the moisture content in the soil and will provide information in the form of an analo signal, as well as the LDR which will ce an analog signal received from the amount of sunlight captured an received by Aduino Uno. After Arduino Uno reads it, then will be displa the LCD in the form of soil moisture percentage and the amount of LUX / Keywords: Soil Moisture, Plant, Arduino Uno, Sun, Light.